Changes in Metamorphopsia, Visual Acuity, and Central Macular Thickness after Epiretinal Membrane Surgery in Four Preoperative Stages Classified with OCT B-Scan Images. (17th June 2019) - Mao, Jianbo; Wu, Hanfei; Liu, Chenyi; Zhu, Chenting; Lao, Jimeng; Chen, Yiqi; Tao, Jiwei; Zhang, Yun; Shen, Lijun
Abstract : Purpose . To observe the changes in metamorphopsia, visual acuity, and central macular thickness (CMT) in patients undergoing vitrectomy for idiopathic epiretinal membranes (iERM); all of which were preoperatively stratified into 4 stages according to the anatomical structure of the macula seen on the optical coherence tomography (OCT) b-scan images. Methods . A total of 108 eyes of 106 patients were included. We evaluated and classified the severity of each preoperative ERM based on OCT. Changes in the best-corrected visual acuity (BCVA), metamorphopsia, and CMT were studied by comparing the pre- and postoperative measurements. The follow-up time was at least 6 months. Results . There were 41 eyes at stage 2, 35 at stage 3, 32 at stage 4, and none at stage 1. BCVA and metamorphopsia significantly improved at the final visit in all patients (P < 0.01 ). However, comparing the pre- and postoperative measurements at each stage, only the BCVA and CMT improved significantly for all stages (P < 0.001 ). For stages 2 and 3 ERMs, the horizontal (MH) and vertical (MV) metamorphopsia scores decreased significantly after surgery (P < 0.05 ). No significant difference was found in either MH or MV for stage 4 ERMs (P both >0.05). The preoperative BCVA, MH, and CMT had significant difference among the three stages (P < 0.05 ). Similarly, the postoperative values in the three variables mentioned above also had significant difference among the three stages (P < 0.05 ). For stage 2 ERMs, the baseline MH and MV were positively correlated with the baseline CMT. The MH and MV at the final follow-up also presented a significant positive correlation with the baseline CMT. For stage 3 ERMs, only the baseline MV showed significant correlation with the CMT. Conclusion . Categorization of the preoperative ERMs is a useful method to predict the postoperative improvement in metamorphopsia, which would aid in surgical decisions for patients with ERMs.